Dose-proportional pharmacokinetic properties of GLA5PR GLARS-NF1 controlled-release pregabalin in healthy Korean volunteers: a randomized, open, single-dose, parallel study - Shin KH; Jeon JY; Jang K; Kim TE; Kim MG (Dove Medical Press, 2018)
Kwang-Hee Shin,1 Ji-Young Jeon,2 Kyungho Jang,2 Tae-Eun Kim,3 Min-Gul Kim2,4 1College of Pharmacy, Research Institute of Pharmaceutical Sciences, Kyungpook National University, Daegu, Republic of Korea; 2Center for Clinical Pharmacology and Biomedical Research Institute, Chonbuk National University Hospital, Jeonju, Republic of Korea; 3Department of Clinical Pharmacology, Konkuk University Medical Center, Seoul, Republic of Korea; 4Department of Pharmacology, School of Medicine, Chonbuk National University, Jeonju, Republic of Korea Purpose: The aim of this study was to evaluate the dose-proportional pharmacokinetic characteristics of pregabalin following the administration of GLA5PR GLARS-NF1 tablets (150, 300, 450, and 600 mg) in the fed state.Subjects and methods: An open-label, randomized, single-dose, parallel study was conducted in 40 eligible subjects who were randomly assigned to receive a single 150, 300, 450, or 600 mg dose of GLA5PR GLARS-NF1. Serial blood samples were collected before and after dosing for 36 hours, and plasma concentrations were determined using liquid chromatography-tandem mass spectrometry. Safety profiles were evaluated throughout the study (trial registration number: NCT02327000).Results: Thirty-seven subjects completed the studies. The area under the plasma concentration-time curve up to the last measurable concentration of pregabalin exhibited dose proportionality following administration of GLA5PR GLARS-NF1 tablets from 150 to 600 mg while its maximum plasma concentration showed dose proportionality at a dose range of 150–450 mg. The safety evaluations showed no clinically significant finding after administration of GLA5PR GLARS-NF1 tablets (150, 300, 450, and 600 mg) in the fed state.Conclusions: The dose-proportional properties of GLA5PR GLARS-NF1 150–450 mg tablets were determined. Keywords: gamma-aminobutyric acid analog, GABA analog, maximum concentration, safety evaluation, Korean